The importance of institutions in expansionary fiscal consolidations: A critical assessment of non-Keynesian effects - István Benczes (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The short-term effects of fiscal consolidation have attracted an increasing attention from both the academia and policy makers in the recent years. Authors in the literature on non-Keynesian effects usually put the emphasis on the need for the devaluation of the national currency, the accommodating reaction of the monetary authority and the favourable international economic conditions as the necessary accompanying tools of fiscal consolidation, in order to realise short-term expansionary effects. Some also add the necessity of large-scale adjustment; while others support the view that a high and increasing debt ratio or increasing government spending, by triggering an unavoidable adjustment, is the key to experiencing short-term expansionary effects. The composition of adjustment also became a crucial explanation for non-Keynesian effects. However, as the following critical assessment of the literature on expansionary fiscal consolidations will reveal, institutional conditions, such as the importance of the depth of financial intermediation and the influencing role of labour market structure, can prove to be crucial in the occurrence of the desired expansionary short-term effects.
Keywords: E62; E65; 330; fiscal consolidation; non-Keynesian effects; liquidity constraints; social pacts; Haushaltskonsolidierung; Finanzpolitik; Liquiditätsbeschränkung; Konsumtheorie